Effects of Bilingualism on Verbal and Nonverbal Memory Measures in Mild Cognitive Impairment. (18th October 2018) - Rosselli, Mónica; Loewenstein, David A.; Curiel, Rosie E.; Penate, Ailyn; Torres, Valeria L.; Lang, Merike; Greig, Maria T.; Barker, William W.; Duara, Ranjan
Abstract: Objectives: Maintaining two active languages may increase cognitive and brain reserve among bilingual individuals. We explored whether such a neuroprotective effect was manifested in the performance of memory tests for participants with amnestic mild cognitive impairment (aMCI).Methods: We compared 42 bilinguals to 25 monolinguals on verbal and nonverbal memory tests. We used: (a) the Loewenstein-Acevedo Scales for Semantic Interference and Learning (LASSI-L), a sensitive test that taps into proactive, retroactive, and recovery from proactive semantic interference (verbal memory), and (b) the Benson Figure delayed recall (nonverbal memory). A subsample had volumetric MRI scans.Results: The bilingual group significantly outperformed the monolingual group on two LASSI-L cued recall measures (Cued A2 and Cued B2). A measure of maximum learning (Cued A2) showed a correlation with the volume of the left hippocampus in the bilingual group only. Cued B2 recall (sensitive to recovery from proactive semantic interference) was correlated with the volume of the hippocampus and the entorhinal cortex of both cerebral hemispheres in the bilingual group, as well as with the left and right hippocampus in the monolingual group. The memory advantage in bilinguals on these measures was associated with higher inhibitory control as measured by the Stroop Color-Word test.Conclusions: Our results demonstrated a superior performance of aMCI bilinguals over aMCI monolinguals on selected verbal memory tasks. This advantage was not observed in nonverbal memory. Superior memory performance of bilinguals over monolinguals suggests that bilinguals develop a different and perhaps more efficient semantic association system that influences verbal recall. ( JINS, 2019, 25, 15–28)